Water-based binder composition and its application
Patent Information
- Application Number
- JP2023570305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2022-05-12
- Publication Date
- 2025-04-18
AI Technical Summary
Existing aqueous binder compositions for secondary batteries, particularly those using styrene butadiene rubber (SBR) and acrylic rubber (ACR), do not self-thicken, leading to the need for additional rheology modifiers that increase raw material costs, electrode volume, and reduce energy density due to volatile organic compounds (VOCs) and gas generation during large-scale manufacturing.
Aqueous electrode-forming slurry compositions utilize self-thickening polymer latex particles as a binder, eliminating the need for rheology modifiers, thereby improving adhesion, dispersion, and reducing resistivity while minimizing VOCs and gas generation.
The self-thickening polymer latex particles enhance electrode adhesion, interconnectivity, and reduce resistivity, resulting in higher energy density and safer large-scale anode production without the use of additional additives.
Smart Images

Figure 2022241066000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous binder composition useful in the manufacture of negative electrodes for secondary batteries. The present invention also relates to negative electrodes made with the binder composition, and to electrochemical storage devices using the negative electrodes. [Background technology]
[0002] The statements and references in this section are for background purposes only and should not be considered prior art.
[0003] Secondary (rechargeable) batteries, such as lithium-ion secondary batteries, are used as power sources for home appliances as well as electric vehicles. In the manufacture of electrodes for such secondary batteries, water-based slurries are often preferred over solvent-based slurries due to environmental concerns. Typically, these electrodes are manufactured by dispersing the electrode-forming components in water, casting the slurry or paste as a thin film onto a current collector, and then drying the film to form the electrode. The function of the polymer binder is to bind the electrode-forming particulates onto the current collector.
[0004] Rheology modifiers are typically present in the slurry formulation to adjust the slurry rheology for the electrode manufacturing casting process. Examples of rheology modifiers used in electrode formulations include, but are not limited to, neutralized carboxymethyl cellulose (CMC) and / or neutralized polyacrylic acid (PAA). The use of rheology modifier additives in the slurry increases raw material costs, requires additional processing steps, and occupies space in the electrode, increasing the volume and weight of the battery. All of these negatively impact the energy density and cost of the battery. Therefore, the elimination of rheology modifier additives is highly desirable.
[0005] Carbon nanotubes (CNTs) are increasingly being applied as conductive additives in electrode formulations because their high electronic conductivity and high aspect ratio enable them to form a continuous conductive network in the active layer of the electrode, which reduces the electrode's resistivity and polarization and helps improve battery performance. In addition, CNTs have good physical elasticity, which acts as a mechanical reinforcement between the electroactive materials in the active layer, suppressing cracking and crumbling and contributing to the overall integrity of the electrode. A technique to maximize the potential of CNTs in an electrode is to uniformly disperse them in the slurry. Without being bound by any theory, it is believed that when CNTs are uniformly dispersed in the electrode slurry, they can induce high electronic conductivity in the electrode and can withstand the resulting micro-fracture of the electrode, which allows the amount of conductive carbon and binder to be further reduced in the electrode formulation without compromising the electrode's performance. Furthermore, reducing the amount of inactive components ultimately increases the electrode energy density, which is favorable for battery applications.
[0006] US 2020 / 0203707 discloses an electrodepositable coating composition comprising: a binder having a pH dependent rheology modifier comprising residues of a crosslinking monomer and / or a monoethylenically unsaturated alkylated alkoxylate monomer; an electrochemically active material and / or a conductive agent; and an aqueous medium. US 2020 / 0203704 discloses an electrodepositable coating composition comprising a fluoropolymer; an electrochemically active material and / or a conductive agent; a pH dependent rheology modifier; and an aqueous medium comprising water.
[0007] US 2013 / 0330622 discloses an anode for a secondary battery comprising an anode active material, a binder, and a water-soluble polymer. The water-soluble polymer can be a copolymer containing 15% to 50% by weight of ethylenically unsaturated carboxylic acid monomer units, 30% to 70% by weight of (meth)acrylic acid ester monomer units, and 0.5% to 10% by weight of fluorine-containing (meth)acrylic acid ester monomer units. Summary of the Invention [Problem to be solved by the invention]
[0008] Existing styrene butadiene rubber (SBR) and acrylic rubber (ACR) binders (such as those used in U.S. Patent Application Publication No. 2013 / 0330622) do not self-thicken because they do not contain enough ionized monomers.
[0009] It has been reported in the literature that during the preparation of aqueous slurries for lithium-ion battery applications, amorphous silicon (Si) can be oxidized to produce H2 gas [K.Hays et al; J.Phys.Chem.C2018,122,18,9746-9754]. The use of Si in secondary batteries is important because it has the potential to increase the energy density of the negative electrode of Li-ion batteries. However, the production of H2 poses safety concerns during large-scale battery manufacturing.
[0010] Therefore, there remains a need for a water-based binder composition for preparing a slurry of active material and conductive particles that provides suitable rheological properties, no H2 evolution, low Tg and minimum film formation temperature (MFFT), but does not contain additional additives that are not electrochemically active, such as rheology modifiers or significant amounts of coalescents, which lead to undesirable weight gain (reduced energy density) and increased volatile organic compounds (VOCs) in the battery.
[0011] It is an object of the present invention to provide novel compositions comprising polymeric binders for use in electrodes of secondary electrochemical electrical energy storage devices. [Means for solving the problem]
[0012] Surprisingly, it has been found that an electrode-forming slurry composition with suitable rheological properties can be achieved by using only self-thickening polymer latex particles as a unique binder without the need for additional rheological modifier additives. Thus, the unique binder of the present invention in the electrode-forming slurry composition can replace both SBR and carboxymethyl cellulose (CMC) in standard slurry formulations. Even more surprisingly, anodes made with this electrode-forming slurry composition exhibit high adhesion to current collectors, no H2 evolution, and lower resistivity compared to the state of the art described in the literature. Anodes formed from the electrode-forming slurry composition of the present invention exhibit high adhesion, high interconnectivity, and high irreversibility as a result of the water-based self-thickening binder.
[0013] The polymer latex particles contained as a unique binder in the electrode-forming slurry composition of the present invention can promote better dispersion of CNTs in the slurry due to its novel chemical composition and self-thickening property, which can improve the dispersion of CNTs during the compounding process to control the rheological properties of the slurry composition without the inclusion of CMC and / or polyacrylic acid (PAA), or rheological additives.
[0014] Unexpectedly, the binder of the present invention prevents H2 gas evolution during the preparation of the amorphous Si-containing aqueous slurry, which is an advantage for large-scale anode production.
[0015] The present invention relates to an aqueous electrode-forming slurry composition having aqueous self-thickening polymer latex particles as a binder for producing electrodes, particularly negative electrodes (anodes) for use in electrodes of non-aqueous electrochemical devices such as batteries and double layer capacitors. The aqueous electrode-forming slurry composition comprises aqueous self-thickening polymer latex particles as a binder and one or more solid particulate powdered anode-forming materials. In one embodiment, the self-thickening polymer latex particles advantageously have a Tg of less than 55° C. and an acid value (mg of KOH equivalent) of 40 to 400 mg KOH, where at least 10% of the acid groups of the ethylenically unsaturated monomers containing at least one acid functional group are in neutralized form. Furthermore, the polymer latex particles do not contain fluorinated or butadiene monomers polymerized therein. In another embodiment, the electrode-forming slurry composition does not contain carboxymethyl cellulose (CMC), additional rheology modifier additives, fluorine-containing binders, and / or monomers containing conjugated double bonds. In another embodiment, the pH of the self-thickening binder is 9 to 2, preferably 8 to 3, and more preferably 7 to 4. In another embodiment, the electrode-forming slurry composition contains very little or no volatile organic compounds (VOCs), or contains less than 5 parts, or less than 2 parts, or less than 1 part, or less than 0.5 parts of VOCs and / or adhesion promoters and / or coalescents. In another embodiment, the electrode-forming slurry composition does not contain CMC, additional rheology-controlling additives, fluorine-containing binders, and / or polymers containing conjugated double bonds, the pH of the self-thickening binder is less than 5, and the electrode-forming slurry composition contains very little or no VOCs.
[0016] A slurry composition for forming an electrode is provided. The slurry composition for forming an electrode comprises: a) 10-300 parts of one or more particulate electrode-forming materials; b) 0.1-60 parts of polymeric latex particles; and c) 100 parts of water. The slurry composition for forming an electrode is capable of forming an electrode. The polymeric latex particles b) comprise at least one ethylenically unsaturated monomer containing at least one acid functional group, and no fluorinated or butadiene monomers are polymerized therein. The polymeric latex particles b) have the following properties: · Tg below 55°C and / or minimum film formation temperature below 25°C; · Volume average particle size less than 500 nm; in one embodiment a pH of 9 to 2, in one embodiment a pH of 8 to 3, in another embodiment a pH of 7 to 4; an acid number between 40 and 400 mg KOH equivalents such that at least 10% of the acid functional groups of the ethylenically unsaturated monomers in the polymer latex particles are neutralized; and 5% by weight of polymer latex particles in water for 10s -1 and a viscosity of at least 1000 cP at 25°C.
[0017] The electrode forming slurry composition may include the following optional components: 0-10 parts of one or more additives selected from the group consisting of anti-settling agents, surfactants, and mixtures thereof; 0-5 parts of one or more wetting agents; 0-5 parts of one or more dispersants; 0-5 parts, very low or no volatile organic compounds (VOCs), or less than 5 parts, or less than 2 parts, or less than 1 part, or less than 0.5 parts of one or more VOCs, and / or adhesion promoters and / or coalescents; although, as mentioned above, due to the specific structure of the binders described in this disclosure, it is preferred that no coalescents are included or required. 0-5 parts of rheology modifier additives, although again, these are preferably not included and are not required due to the specific structure of the binders described in this disclosure.
[0018] Further areas of applicability will become apparent from the description provided herein. It should be understood that the description and specific examples are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The purpose of the binder is to provide adhesive and cohesive strength to the matrix of particulate electrode-forming materials, which typically include active material (material capable of accepting lithium ions) and conductive material. The polymeric latex particles disclosed as binders contain a relatively high percentage of acid functional groups. The polymeric latex particles disclosed as binders may also contain other monomers.
[0020] The compositions for use as electrodes disclosed herein may be in the form of a solution, dispersion, or paste, but are typically prepared as slurries. Thus, the formation of an electrode can be accomplished by applying a layer of the electrode-forming slurry composition to a current collector. The conductive electrode-forming slurry composition layer is then dried to form a layer of electrode material adhered to the current collector.
[0021] As used herein, the term "electrode" refers to a dried layer of an electrode-forming slurry composition cast onto a current collector. Typically, electrodes are manufactured by casting a slurry or paste of dispersed electrode-forming components and binder as a thin film and then drying the film to form the electrode. This dried film is referred to as the electrode.
[0022] As used herein, the term "electrode assembly" refers to a combination of a current collector and a dried electrode dried thereon. A slurry or paste of dispersed electrode-forming components and binder can be cast onto a current collector, such as copper or nickel foil, to form an electrode assembly. The electrode assembly can be further coated with a separator-forming slurry, such as alumina and binder dispersed in water. The separator slurry can be cast simultaneously with the electrode slurry in a one-step process using a dual or multi-die in a wet-on-wet process. Alternatively, the separator slurry can be cast onto the electrode after the electrode is dried, or a free-standing separator can be adhered to the electrode surface. Thus, the electrode assembly includes a current collector, a dried electrode film, and optionally a separator film on the top surface of the electrode.
[0023] The function of the polymer binder is to bind the electrode-forming particulates onto the current collector and to provide mechanical properties during use of the battery.
[0024] Compositions for use as electrodes can be deposited by any method known in the art. Non-limiting examples of such application methods include spraying, rolling, drawdown bar application, bird bar application, gravure, slot coating, or other coil coating methods. The composition is dried (optionally with heat) to remove water and other volatile materials. The coating of the composition may be optionally calendered after the drying step to reduce its porosity. The drying time, temperature, and vacuum used can be adjusted to achieve the desired drying.
[0025] The current collector may be in the form of a mesh, foam, foil, rod, or another structural form that does not interfere with the function of the current collector. The current collector material depends on whether the electrode is positive (cathode) or negative (anode). The most common current collectors for the negative electrode are sheets or foils of copper (Cu) or nickel (Ni) metal. The electrode material for the anode must be applied and adhered to the surface of the current collector to form the anode assembly.
[0026] As used herein, the term "slurry" refers to a free-flowing or free-flowing and / or pumpable suspension of finely divided solid materials and binders in water. Such finely divided solids may include, among others, polymeric binder particles, in addition to solid particles that are typically electrochemically active and conductive materials necessary to form electrodes for secondary batteries. Additives may also be dissolved in the water.
[0027] As discussed above, an electrode-forming slurry composition is provided. The electrode-forming slurry composition includes: a) 10-300 parts of one or more particulate electrode-forming materials; b) 0.1-60 parts of polymer latex particles; and c) 100 parts of water. The electrode-forming slurry composition is capable of forming an electrode. The polymer latex particles b) include i) at least one ethylenically unsaturated monomer that includes at least one acid functional group, and ii) no fluorinated monomer or butadiene monomer is polymerized therein.
[0028] The polymer latex particles b) have the following properties: · Tg below 55°C and / or minimum film formation temperature below 25°C; · Volume average particle size less than 500 nm; in one embodiment a pH of 9 to 2, in one embodiment a pH of 8 to 3, in another embodiment a pH of 7 to 4; i) an acid value of 40 to 400 mg KOH equivalents such that 10% of at least one ethylenically unsaturated monomer containing at least one acid functional group in the polymer latex particles b) is neutralized; and 5% by weight of polymer latex particles in water for 10s-1 and a viscosity of at least 1000 cP at 25°C.
[0029] The electrode forming slurry composition may include the following optional components: d) 0 to 5 parts of one or more wetting agents; e) 0 to 5 parts of one or more dispersants; f) 0 to 5 parts of one or more VOCs, very low or no volatile organic compounds (VOCs), or less than 5 parts, or less than 2 parts, or less than 1 part, or less than 0.5 parts VOCs, and / or adhesion promoters and / or film-forming agents. g) 0 to 5 parts of a rheology modifier additive; and h) 0 to 10 parts of one or more additives selected from the group consisting of anti-settling agents, surfactants, and mixtures thereof.
[0030] An electrode film for a lithium ion battery and / or a lithium ion capacitor may include a) a particulate or powdered anode-forming material, and b) polymer latex particles that serve as a binder material.
[0031] Advantageously, the electrode-forming slurry composition of the present invention is preferably free of carboxymethylcellulose (CMC) and / or fluorine-containing binders, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethylene chlorotrifluoroethylene (ECTFE), polyethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), perfluoroalkoxy (PFA), polychlorotrifluoroethylene (PCTFE), fluoroacrylates, or fluorosilicones. Fluorine-containing polymers are relatively very expensive and generally have low surface energy or low adhesion, which reduces the effectiveness of the binder. The electrode-forming composition is also preferably free of conjugated double bond-containing polymers, such as those containing butadiene, isoprene, and / or chloroprene as monomers or comonomers. Polymers containing conjugated double bonds are prone to oxidation, which reduces the life and usefulness of the polymer. The electrode-forming composition is preferably free of any rheological additives, except for the self-thickening binder of the present disclosure.
[0032] Particulate anode forming material a) The electrode-forming slurry composition disclosed herein includes 10 to 500 parts of one or more particulate anode-forming materials based on 100 parts of water. In one embodiment, the electrode-forming slurry can include 20 to 400 parts of one or more particulate anode-forming materials per 100 parts of water. In one embodiment, the electrode-forming slurry can include 30 to 300 parts of one or more particulate anode-forming materials per 100 parts of water. In one embodiment, the electrode-forming slurry can include 50 to 200 parts of one or more particulate anode-forming materials per 100 parts of water.
[0033] Particulate anode-forming materials include, but are not limited to, conductive carbon additives, carbon nanotubes (CNTs), artificial graphite, natural graphite, hard carbon, activated carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semicrystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate, mixtures or composites of the above materials, and / or other materials known in the art or described herein as suitable for use as an anode in a lithium-ion battery. These particulates may include active materials, i.e., materials capable of inserting (accepting) lithium ions, and conductive materials. Lithium-ion capacitor and / or lithium-ion battery electrode films may include about 80 weight percent, preferably up to 94 weight percent, more preferably up to 98 weight percent of particulate anode-forming materials after drying. These anode-forming materials are typically in the form of solid powders.
[0034] Conductive carbon materials such as carbon black and graphite powder are widely used in positive and negative electrodes to reduce the internal electrical resistance of electrochemical systems. Non-limiting examples of conductive carbon may include furnace black, acetylene black, CNT, fine graphite powder, evaporated graphite fiber, and Ketjen carbon black. The typical addition level of conductive carbon to the active material in the electrode-forming material a) is usually in the range of 0.1% to 20% by weight, more preferably in the range of 0.5% to 10% by weight, based on the total amount of particulate anode-forming material.
[0035] a) The amount of particulate anode-forming material (including both active material and conductive carbon) present in the electrode-forming slurry composition can be from 50% to 99% by weight of the total dry weight of the composition, preferably from 80% to 98% by weight, and most preferably from 94% to 98% by weight of the total dry weight of the composition.
[0036] Polymer latex particles b) The electrode-forming slurry composition further comprises polymer latex particles b) as a binder. The binder is present in the electrode, and one of the main functions of the binder is to bind the active material and the conductive material and to contribute to adhering the electrode to the current collector.
[0037] The polymer latex particles b) are present in the electrode-forming slurry composition in a ratio of 0.1 to 20 parts per 100 parts of water c) in the electrode-forming slurry composition. In one embodiment, the polymer latex particles b) are present in the electrode-forming slurry composition in a ratio of 0.5 to 20 parts per 100 parts of water c) in the electrode-forming slurry composition, in another embodiment, 1 to 15 parts, and in another embodiment, 2 to 10 parts.
[0038] The inventors have surprisingly found that the Tg of the disclosed polymer latex particle b) binder should be within a desired range to balance the mechanical properties of the polymer latex particle b) binder. The Tg is the temperature at which the physical properties of the plastic change from thermoplastic (e.g., flexible, soft, stretchable) to glassy state physical properties that limit the flexibility and elongation of the polymer binder b). As a result, bending the electrode can result in the formation of cracks (visible or microcracks) in the electrode, reducing the performance of the electrode. Above the Tg, the polymer latex particle b) binder behaves like a rubber-like material that can accommodate flexibility and elongation. Thus, the properties of the polymer latex particle b) binder can vary significantly above and below its Tg. To facilitate easy handling of the electrode and to obtain good electrode performance, the Tg of the polymeric latex particles b) is around or preferably below room temperature, i.e. according to certain embodiments below 55°C, below 45°C, below 35°C, below 25°C, below 20°C, or below 10°C.
[0039] Without being bound by any theory without limiting the scope of the present invention, to obtain satisfactory electrode integrity using the electrode-forming composition disclosed herein, when the aqueous phase evaporates, the polymeric latex particles b) constituting the binder particles can coalesce to form a continuous network, holding the active material and conductive carbon in an interconnected electrode network. The minimum film-forming temperature (MFFT) of the polymeric latex particles b) binder is the lowest temperature at which coalescence of the polymeric particles occurs when the water evaporates to form a continuous film. The MFFT is the lowest temperature at which the polymeric binder b) particles coalesce to form a continuous film. The polymeric latex particles b) binder advantageously have a MFFT at or below room temperature, i.e., according to certain embodiments, preferably below 55°C, more preferably below 50°C, less than 45°C, even more preferably below 35°C, most preferably below 25°C, or even below 20°C.
[0040] Because of the desirable Tg of the polymeric latex particles b), there is little or no need to add a coalescing agent that contributes to the volatile organic content (VOC) of the electrode-forming slurry composition of the present invention. In one embodiment, the electrode-forming composition has a VOC content of 0 to less than 5 wt%, in another embodiment, 0 to less than 1 wt%, and in yet another embodiment, 0 to less than 0.1 wt%.
[0041] Thermal analysis using a differential scanning calorimeter (DSC) can provide a convenient method to measure the glass transition temperature (Tg) of the polymer latex particles b) as a binder after drying. Measurements are performed using a standard heating rate of 10 °C / min according to ATSM-D3418-15 (2018). Measured glass transition temperatures reported in this disclosure are measured during the second heating cycle unless otherwise noted. Estimated glass transition temperatures reported here are calculated using the Fox equation.
[0042] The polymer latex particles b) have as polymerizable monomers: i) comprises at least one ethylenically unsaturated monomer containing at least one acid functional group; and ii) no fluorinated monomers or monomers containing conjugated double bonds are polymerized therein. Non-limiting examples of such monomers that are not included in certain embodiments include butadiene, isoprene, vinyl fluoride, tetrafluoroethylene, vinylidene fluoride, chlorotrifluoroethylene, hexafluoropropylene, perfluoropropyl vinyl ether, perfluoromethyl vinyl ether, fluoroacrylate monomers, and mixtures thereof.
[0043] In one embodiment, the polymeric latex particles b) may have a volume average particle size of less than 500 nm, in another embodiment less than 250 nm, and in another embodiment less than 150 nm.
[0044] i) an ethylenically unsaturated monomer containing at least one acid functional group; With regard to the at least one ethylenically unsaturated monomer i) comprising at least one acid functional group, it has been found that in particular the carboxylic acid functional group-containing monomers comprised as monomer i) in the polymer latex particles b) can be used in the polymer latex particles forming the binder for the anode, resulting in significant advantageous effects.Other suitable acid groups in addition to the carboxylic acid groups that may be comprised in the at least one ethylenically unsaturated monomer comprising at least one acid functional group are sulfonic acid groups and sulfuric acid groups, or phosphonic acid groups and phosphoric acid groups.
[0045] Non-limiting examples of suitable ethylenically unsaturated monomers i) containing at least one acid functional group include, but are not limited to, (meth)acrylic acid, β-carboxyethyl acrylate, 4-styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and monoesters of itaconic acid, maleic acid, fumaric acid, and mixtures thereof.
[0046] For example, 10% to 60% by weight of the total polymerized monomers in the polymer latex particles b) can be i) at least one ethylenically unsaturated monomer comprising at least one acid functional group. In one embodiment, the polymer latex particles can be 20% to 55% by weight, in another embodiment 25% to 45% by weight, and in yet another embodiment 30% to 55% by weight of the total polymerized monomers in the polymer latex particles b) can be at least one ethylenically unsaturated monomer comprising at least one acid functional group i).
[0047] In contrast to some of the references cited above, the self-thickening polymer latex particles b) that function as binders in the electrode-forming slurry composition are partially neutralized prior to making the electrode-forming composition or as a first step in making the electrode-forming composition (by adding a base such as ammonia solution, lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. to the aqueous polymer latex particles b) (binder) to reach a suitable slurry viscosity).
[0048] These polymer latex particles b) are self-thickening because under acidic conditions, the self-thickening polymer latex particles b) used as binders in the electrode-forming composition are in the form of an emulsion with a very low viscosity of less than 200 cP before being neutralized by a base. Without intending to be bound by any theory, when the self-thickening binder is partially or totally neutralized with a base such as an ammonia solution or a lithium hydroxide solution, it exhibits a self-thickening mechanism due to, for example, an increase in the hydrodynamic volume of the emulsion of the polymer latex particles b).
[0049] In particular, the polymer latex particles a) have an acid value of 40-400 mg KOH equivalent such that at least 10% of the acid functional groups of the at least one ethylenically unsaturated monomer i) containing at least one acid functional group are neutralized. In one embodiment, the acid value is 50-350, in another embodiment 75-325, and in yet another embodiment 100-300 mg KOH equivalent. Thus, preferably at least 10%, more preferably at least 20%, and most preferably at least 30% of the acid groups of the at least one ethylenically unsaturated monomer i) containing at least one acid functional group are neutralized. Thus, a sufficient amount of base can be added to the electrode-forming slurry composition such that the pH of the electrode-forming slurry composition is 9-2, preferably 8-3, more preferably 7-3, and most preferably 7-4. Suitable bases include, but are not limited to, lithium hydroxide, ammonia (ammonium hydroxide), potassium hydroxide, sodium hydroxide, triethylamine, N,N-dimethylethanolamine, n-morpholine, or n-methylmorpholine. Lithium hydroxide is most preferred.
[0050] Thus, the polymer latex particles b) are such that an emulsion of 5% by weight of polymer latex particles in water will melt at 10s when the pH of the emulsion is less than -1 The emulsion has a viscosity of less than 100 cP at a shear rate of 10 s and 25 °C. When a base is added to the emulsion so that the pH of the emulsion is 4 or more, the viscosity of the emulsion increases to 10 s. -1 According to one embodiment, the polymer latex particles b) are self-thickening such that the pH of the emulsion of the polymer latex particles b) in water increases by at least 10 times, or by at least 1000 cP, at a shear rate of 25° C. ... -1 and a viscosity of at least 2000 cP at 25°C.
[0051] Comonomer b) in polymer latex particles To achieve a good balance between binder properties and self-thickening, the polymeric latex particle binder may typically be a copolymer prepared from the acid group-containing monomer i) discussed above and other comonomers.
[0052] Nonionic ethylenically unsaturated monomers ii) For example, certain hydrophobic groups may be included in the polymer particles b), which, upon drying, will act as a robust three-dimensional binder for forming the electrode. Such hydrophobic groups originate from comonomers which may also be present in the polymer latex particles b) as polymerized monomers in addition to the at least one ethylenically unsaturated monomer i) containing at least one acid functional group.
[0053] Suitable such non-ionic ethylenically unsaturated monomers ii) may be water-insoluble lower alkyl esters of (meth)acrylic acid or other acids, and / or associative monomers containing hydrophobic groups, such as hydrophobically modified polyoxyalkylene esters and monomers containing non-ionic groups. Suitable non-ionic ethylenically unsaturated monomers ii) include, but are not limited to: acrylic and methacrylic acid esters, such as C1-C12 (meth)acrylates, (meth)acrylamides, (meth)acrylonitrile, vinyl acetate, styrene and its derivatives, diisobutylene, vinylpyrrolidone, vinylcaprolactam, and mixtures thereof.
[0054] The polymer latex particles b) may contain at least one nonionic ethylenically unsaturated monomer ii) as a polymerization monomer, in an amount of 40 to 90% by weight of the total polymerization monomers. The polymer latex particles b) contain at least one nonionic ethylenically unsaturated monomer ii) as a polymerization monomer, in an amount of preferably 45 to 85% by weight, more preferably 50 to 80% by weight, and most preferably 50 to 75% by weight of the total polymerization monomers.
[0055] Crosslinking monomer iii): To inhibit the infinite expansion of the self-thickening polymer latex particles b), an optional crosslinking agent can be incorporated into the polymer latex particles b) to form a soft microgel.
[0056] The polymer latex particles b) (binder) can be optionally crosslinked by using a crosslinking monomer containing at least two free radically polymerizable ethylenically unsaturated moieties. In one embodiment, the crosslinking agents used in the present invention are typically: polyvinyl aromatic monomers (divinylbenzene, diallyl phthalate); polyalkenyl ethers (triallyl pentaerythritol, diallyl pentaerythritol, diallyl sucrose, octaallyl sucrose, trimethylolpropane diallyl ether); polyunsaturated esters of polyhydric alcohols or polyacids (trimethylolpropane tri(meth)acrylate, trimethylolpropane, polyethylene glycol di(meth)acrylate). In another embodiment, these crosslinking monomers iii) are: pentaerythritol, sorbitol, or sucrose; diacrylic or dimethacrylic esters derived from a polyol selected from pentaerythritol, sorbitol, or sucrose; divinylnaphthalene, trivinylbenzene, 1,2,4-trivinylcyclohexane, triallyl pentaerythritol, diallyl pentaerythritol, diallyl sucrose, trimethylolpropane diallyl ether, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, diaryl itaconate, diallyl fumarate, diallyl maleate, butanediol dimethacrylate, ethylene di(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, trimethylolpropane tri(meth)acrylate, methylene bis(meth)acrylamide, triallyl cyanurate, diallyl phthalate, divinylbenzene, and mixtures thereof. According to another embodiment, these crosslinkers may be selected from DAP; diallyl phthalate; EGDMA; ethylene glycol dimethacrylate; MBA; methylene bisacrylamide; DVB; divinylbenzene; FRA; bicyclopentenyloxyethyl methacrylate APE; trimethylolpropane triallyl ether; and combinations thereof.
[0057] The crosslinking monomer iii) may be present in the polymer latex particles b) at 0.05% to 5% by weight of the total polymerized monomers in the polymer latex particles b), in one embodiment, the crosslinking monomer iii) is present at 0.01% to 4% by weight, in another embodiment, at 0.1% to 3% by weight, and in another embodiment, at 0.1% to 2% by weight of the total polymerized monomers in the polymer latex particles b).
[0058] iv) oxyalkylated monomers having ethylenic unsaturation and terminated with hydrogen or a hydrophobic aryl or alkyl chain having 1 to 60 carbon atoms; The disclosed polymeric binder b) may further contain an oxyalkylated monomer or monomers having ethylenic unsaturation and terminated with a hydrophobic aryl or alkyl chain having from 10 to 60 carbon atoms, having the following formula (iv): [ka] During the ceremony, m and p each represent the number of alkylene oxide units from 0 to 150; n represents the number of ethylene oxide units from 5 to 150; q represents an integer at least equal to 1, 5≦(m+n+p)q≦150, preferably 15≦(m+n+p)q≦120; R1 represents methyl or ethyl; R2 represents methyl or ethyl; R represents a polymerizable unsaturated functional group belonging to the group of acrylic acid, methacrylic acid, maleic acid, itaconic acid, and crotonic acid esters; R' represents a hydrophobic aryl or alkyl chain having 1 to 60 carbon atoms.
[0059] The hydrophobic aryl or alkyl chain in the monomer iv) can provide additional interactions between the polymer latex polymer b) and the anode-forming material a) to improve dispersibility. It can also improve the rheology tuning properties of the electrode-forming composition upon neutralization. In one embodiment, the weight percentage of the oxyalkylated monomer iv) in the disclosed polymer binder b) is preferably in the range of 0.1-15 wt%, in another embodiment, the monomer in the polymer latex particle b) is in the range of 1-10 wt%, and in another embodiment, in the range of 2-7 wt%.
[0060] According to one embodiment, q represents an integer at least equal to 1, such that 15≦(m+n+p)q≦120.
[0061] According to one embodiment, R represents a group selected from the group consisting of acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl, isoprenyl, unsaturated urethane groups, and combinations thereof. According to another embodiment, R represents a group selected from the group consisting of acrylic urethane, methacrylic urethane, α-α'-dimethyl-isopropenyl-benzyl urethane, allyl urethane, and combinations thereof. According to one embodiment, R represents a group selected from the group consisting of acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl and isoprenyl, esters of maleic acid, esters of itaconic acid, esters of crotonic acid, and combinations thereof. According to one embodiment, R represents a methacrylate group.
[0062] Optional components of the electrode forming slurry composition: d) optionally 0 to 5 parts of one or more wetting agents; e) optionally, 0 to 5 parts of one or more dispersants; f) optionally, 0-5 parts of one or more VOCs, very low volatile organic compounds (VOCs), or no volatile organic compounds (VOCs), or less than 5 parts, or less than 2 parts, or less than 1 part, or less than 0.5 parts VOCs, and / or adhesion promoters and / or film formers; g) optionally, 0 to 5 parts of a rheology modifier additive; and h) optionally, 0 to 10 parts of one or more additives selected from the group consisting of anti-settling agents, surfactants, and mixtures thereof.
[0063] Usage: The electrode-forming composition can be used as an active layer on an anode for use in an electrical energy storage device. Also disclosed is an anode having a thickness of at least 10 microns and exhibiting a resistivity in the z-direction of less than 100 Ω·cm, made from a current collector coated on at least one side with the electrode-forming slurry composition disclosed herein in dry form. The resistivity is measured as described in the Examples.
[0064] The anode can be used in an electrical energy storage device containing a non-aqueous electrolyte, the electrical energy storage device including at least one anode being made from a current collector having at least one surface coated with the electrode-forming slurry composition disclosed herein in dry form. The electrical energy storage device is selected from the group consisting of a non-aqueous battery, a capacitor, and a membrane electrode assembly. EXAMPLES
[0065] a-synthesis Example 1: Binder manufacturing An initial charge consisting of 413 g of deionized water and 3.1 g of sodium dodecyl sulfate was introduced into a 1 L reactor. 113 g of methacrylic acid, 204 g of butyl acrylate, and 0.525 g of diallyl phthalate were weighed into a first glass beaker and mixed with 1 g of sodium dodecyl sulfate and 145 g of deionized water. 0.70 g of ammonium persulfate was weighed into a second glass beaker and dissolved in 10 g of deionized water. 0.07 g of sodium bisulfite was weighed into a third glass beaker and dissolved in 40 g of deionized water.
[0066] The contents of the reactor were heated to a temperature of 76 ± 2 °C. The two solutions of persulfate and bisulfite were introduced into the reactor at once. For a period of 2 hours, the monomer from the first beaker was introduced into the polymerization reactor at a temperature of 76 ± 2 °C. Then, 0.106 g of ammonium persulfate dissolved in 20 g of deionized water was introduced into the reactor over a period of 1 hour. It was then allowed to prepare for 1 hour before the medium was cooled and filtered. The details of the composition of the copolymer are given in Table 1.
[0067] Example 2: Binder manufacturing The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0068] Example 3: Binder manufacturing The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0069] Example 4: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0070] Example 5: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0071] Example 6: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0072] Example 7: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0073] Example 8: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0074] Example 9: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0075] b-Comparative slurry formulation Seven 6.5 mm zirconia balls were placed in a 125 mL polyethylene container of a Thinky ARE-310.
[0076] 0.176 g of carbon black (Super P-Li from Timcal) was added with 2.0 g of carboxymethyl cellulose (CMC) solution at 2% solids in water (7H3SF from Ashland Chemicals) and 7.92 g of graphite MCP 15 μm and mixed at 2000 rpm for 2 minutes. Then, 3.0 g of CMC solution was added consecutively and mixed at 2000 rpm for 2 minutes, followed by another CMC solution and mixing to reach a total CMC solution addition of 8.8. Then, 1.76 g of styrene butadiene rubber (SBR) latex at 30% solids (from Zeon) was added and mixed twice for 2 minutes at 2000 rpm.
[0077] The slurry exhibited smooth creamy characteristics, had a solids content of about 47%, a viscosity of 4000 cP at 10 1 / s as measured by Brookfield V-III, and a pH of 4-7.
[0078] c-Example slurry formulation A water-based self-thickening acrylic binder was prepared by diluting 3 g of 30% solids latex with 14 g of water, then adding 4.5-6 g of a 0.5% ammonia solution. The final dispersion contained 4% solids and exhibited a self-thickening effect.
[0079] Seven 6.5mm zirconia balls were placed in a 125mL polyethylene container of a Thinky ARE-310. 0.176g of carbon black (SuperP-Li from Timcal) was added with 2.0g of self-thickening latex and 7.92g of graphite MCP15um and mixed at 2000rpm for 2 minutes. Then 3.0g of self-thickening latex was added consecutively and mixed at 2000rpm for 2 minutes, followed by another self-thickening latex and mixing until a total addition of 9.973 of self-thickening latex was reached. The slurry exhibited smooth creamy characteristics, had a solids content of about 47% and had a viscosity of 4000cP at 101 / sec as measured by Brookfield V-III.
[0080] d-Electrode fabrication and testing The slurry was cast onto copper foil with a wet thickness of about 110 μm and placed in a convection oven at 120° C. for 30 minutes. The electrode was then calendered to reach a porosity of about 30% by volume. The cast composite was then stamp cut into 1.33 cm 2 The samples were prepared with a surface area of 0.09 cm. The thickness of the samples was measured with a micrometer with an accuracy of 0.1 microns. The Instron machine was used to measure three 0.09 cm 2 Resistivity was measured using gold plated electrodes. Circular Au coated contacts were attached to an Instron fixture / chuck using 3M double sided tape. Resistance was measured using a Yokogawa digital resistance meter (755601, 4 probes). Contact pressure was applied at a rate of 20 N / min using an Instron (SOON load cell). All data was recorded manually at various loads. Resistivity ρ is defined as:
number
[0081] Mass loading was measured by punching several 1 / 2 inch circular samples from the dried electrodes supported on copper foil and weighing them on a 5-point balance.
[0082] The electrodes were calendered at very high pressure at room temperature to reach the desired porosity. The porosity of the electrode was back-calculated from its expected value (weight contribution of each component) and the apparent density, which was obtained by measuring the weight and volume of the electrode using a micrometer and a 5-decimal balance.
[0083] The estimated Tg was calculated using the Fox equation.
[0084] MFFT was determined according to ASTM-D2354-10 (2018) entitled "Standard Test Method for Minimum Film Forming Temperature (MFFT) of Emulsion Vehicles" to ensure the flowability and malleability of the resin particles and therefore their ability to coalesce. MFFT data are shown in Tables 1 and 2 (further supporting MFFT data will be generated).
[0085] Adhesion measurements were performed on an Instron using 1-inch wide electrode specimens and 180° peel at a crosshead speed of 50 mm / min according to ASTM-D903 (2017).
[0086] The acid number of a sample is the number of milligrams of potassium hydroxide required to neutralize one gram of sample, measured by potentiometric titration. The measurement follows ASTM D-D664 (2018) by potentiometric titration. In detail, an appropriate amount of latex was weighed into a titration vessel and diluted with a mixture of isopropanol (IPA) and water. The sample was then titrated with KOH to the equivalence point using an automatic titrator such as a Mettler DL50. The volume average particle size was measured by dynamic light scattering using a Nanotrac UPA150 from Microtrac.
[0087] pH was measured with a ColeParmer portable or benchtop pH meter.
[0088] The experimental results are shown in Table 1 (Examples 1 to 9) and Table 2 (Examples 10 to 17).
[0089] [Table 1]
[0090] DAP: diallyl phthalate; EGDMA: ethylene glycol dimethacrylate; MBA: methylene bisacrylamide; DVB: divinylbenzene; FRA: bicyclopentenyloxyethyl methacrylate; APE: trimethylolpropane triallyl ether; AA: acrylic acid; BA: butyl acrylate; MAA: methacrylic acid; EA: ethyl acrylate; AMPS Na: 2-acrylamido-2-methylpropanesulfonic acid sodium salt.
[0091] [Table 2]
[0092] The low Tg, acid-containing comonomers provided electrodes with low resistivity and good peel strength. * :It cracked and I couldn't make a good film.
[0093] DAP: diallyl phthalate; EGDMA: ethylene glycol dimethacrylate; MBA: methylene bisacrylamide; DVB: divinylbenzene; FRA: bicyclopentenyloxyethyl methacrylate; APE: trimethylolpropane triallyl ether; AA: acrylic acid; BA: butyl acrylate; MAA: methacrylic acid; EA: ethyl acrylate; AMPS Na: 2-acrylamido-2-methylpropanesulfonic acid sodium salt.
[0094] Even at higher Tg, the inclusion of an acid-containing monomer in the binder provided low resistivity electrodes with good peel strength.
[0095] The comparative example is from U.S. Patent Application Publication No. 2020 / 0203704, in which ACRYSOL™ ASE-60 was used.
[0096] In some embodiments, the invention can be construed as excluding any element or process that does not materially affect the basic and novel characteristics of the composition or process. Further, in some embodiments, the invention can be construed as excluding any element or process not specified herein.
[0097] Although the invention has been illustrated and described herein with reference to specific embodiments, it is not intended that the invention be limited to the details shown, but rather various modifications of the details can be made within the scope of the claims and equivalents without departing from the invention.
Claims
1. 1. An electrode forming slurry composition comprising: a) 10 to 300 parts of one or more particulate anode-forming materials; b) 0.1 to 60 parts of polymeric latex particles that satisfy the following: i) comprising at least one ethylenically unsaturated monomer containing at least one acid functional group; and ii) no fluorinated monomers or monomers containing conjugated double bonds have been polymerized therein; wherein the polymer latex particles b) are a Tg of 55° C. or less and / or a minimum film-forming temperature of 25° C. or less; a volume average particle size of less than 500 nm; and an acid number of 40 to 400 mg KOH equivalents such that at least 10% of the acid functionality of at least one ethylenically unsaturated monomer containing at least one acid functionality is neutralized; having 5% by weight of polymer latex particles b) in water at pH 3-7 for 10s -1 has a viscosity of at least 1000 cP at a shear rate of 25°C; c) 100 parts water; d) optionally 0 to 5 parts of one or more wetting agents; e) optionally 0 to 5 parts of one or more dispersants; f) optionally 0-5 parts of one or more VOCs, and / or adhesion promoters, and / or coalescents; g) optionally 0 to 5 parts of a rheology modifier additive; and h) optionally 0 to 10 parts of one or more additives selected from the group consisting of anti-settling agents, surfactants, and mixtures thereof; Here, the electrode forming slurry composition can form an electrode.
2. 2. The electrode-forming slurry composition according to claim 1, wherein the polymer latex particles b) contain as polymerized monomers: 10% to 60% by weight of total polymerized monomers of i) at least one ethylenically unsaturated monomer containing at least one acid functional group, and and from 40 to 90 weight percent, by weight of the total polymerized monomers, of ii) at least one nonionic ethylenically unsaturated monomer.
3. The electrode-forming slurry composition according to claim 1, wherein i) the ethylenically unsaturated monomer containing at least one acid functional group is selected from the group consisting of (meth)acrylic acid, β-polycarboxyethyl acrylate, 4-styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, vinylphosphonic acid, vinylsulfonic acid, itaconic acid, maleic acid, monoesters of fumaric acid, and mixtures thereof.
4. ii) the at least one nonionic ethylenically unsaturated monomer is selected from the group consisting of C1 to C12 (meth)acrylates, (meth)acrylamides, (meth)acrylonitrile, vinyl acetate, styrene and its derivatives, diisobutylene, vinylpyrrolidone, vinylcaprolactam, and mixtures thereof.
5. The polymer latex particles b) further comprise, as polymerized monomers: iii) 0.05% to 5% by weight of the total polymerized monomers of at least one monomer containing at least two free-radically polymerizable ethylenic unsaturations. The electrode forming slurry composition according to claim 1 , comprising:
6. The at least one monomer iii) containing at least two free radically polymerizable ethylenic unsaturations is selected from the group consisting of: allyl ethers derived from a polyol selected from pentaerythritol, sorbitol, or sucrose; diacrylic or dimethacrylic esters derived from a polyol selected from pentaerythritol, sorbitol, or sucrose; divinylnaphthalene, trivinylbenzene, 1,2,4-trivinylcyclohexane, triallyl pentaerythritol, diallyl pentaerythritol, divinyl naphthalene, trivinyl benzene, 1,2,4-trivinylcyclohexane, triallyl pentaerythritol, diallyl pentaerythritol, divinyl naphthalene, trivinyl benzene, 1,2,4-trivinylcyclohexane, trivinyl naphthalene ... erythritol, diallyl sucrose, trimethylolpropane diallyl ether, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, diaryl itaconate, diallyl fumarate, diallyl maleate, butanediol dimethacrylate, ethylene di(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, trimethylolpropane tri(meth)acrylate, methylene bis(meth)acrylamide, triallyl cyanurate, diallyl phthalate, divinylbenzene, and mixtures thereof; 2. The electrode-forming slurry composition according to claim 1, wherein the polymer latex particles b) contain 0.05 to 10% by weight of the total polymerized monomers in the polymer latex particles b).
7. The electrode-forming slurry composition according to claim 1 , wherein the polymer latex particles b) further comprise, as a polymerization monomer: iv) 0.1 to 15% by weight of at least one oxyalkylated monomer having ethylenic unsaturation and terminated with hydrogen or a hydrophobic aryl or alkyl chain having 1 to 60 carbon atoms and having the formula: 【Chemistry 1】 During the ceremony, m and p represent the number of alkylene oxide units from 0 to 150; n represents the number of ethylene oxide units from 5 to 150; q represents an integer at least equal to 1, and 5≦(m+n+p)q≦150; R 1 and R 2 represents methyl or ethyl; R represents at least one polymerizable olefinic unsaturation, preferably a group selected from acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl, isoprenyl, unsaturated urethane groups, in particular acrylic urethane, methacrylic urethane, α-α′-dimethyl-isopropenyl-benzyl urethane, allyl urethane, more preferably a group selected from acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl and isoprenyl, esters of maleic acid, esters of itaconic acid, esters of crotonic acid, even more preferably methacrylate groups and mixtures thereof, R' represents hydrogen or a hydrophobic aryl or alkyl chain end having 1 to 60 carbon atoms.
8. The electrode-forming slurry composition according to claim 7 , wherein q represents an integer of 1 or more, and 15≦(m+n+p)q≦120.
9. 8. The electrode forming slurry composition according to claim 7, wherein R represents a group selected from the group consisting of acrylate, methacrylate, acryl urethane, methacryl urethane, vinyl, allyl, methallyl, isoprenyl, unsaturated urethane groups, and combinations thereof.
10. 8. The electrode-forming slurry composition according to claim 7, wherein R represents a group selected from the group consisting of acrylic urethane, methacrylic urethane, α-α'-dimethyl-isopropenyl-benzyl urethane, allyl urethane, and combinations thereof.
11. 8. The electrode-forming slurry composition according to claim 7, wherein R represents a group selected from the group consisting of acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl and isoprenyl, esters of maleic acid, esters of itaconic acid, esters of crotonic acid, and combinations thereof.
12. The electrode forming slurry composition of claim 7 , wherein R represents a methacrylate group.
13. 5% by weight of latex particles b) in water at pH 3-7 for 10s -1 2. The electrode forming slurry composition of claim 1, having a viscosity of at least 2000 cP at a shear rate of 1000 s at 25°C.
14. The polymer latex particles b) are obtained by subjecting an emulsion of 5% by weight of polymer latex particles in water at a pH of 4 or less to 10 s -1 At a shear rate of 100 s, the emulsion has a viscosity of less than 100 cP at 25° C., and when a base is added to the emulsion to adjust the pH to 3 to 7, the emulsion viscosity is reduced to less than 100 cP at 25° C. -1 2. The electrode forming slurry composition of claim 1, which is self-thickening such that it increases in shear rate to at least 1000 cP at 25°C.
15. 2. The electrode forming slurry composition according to claim 1, wherein the pH of the slurry composition is less than 7, more preferably less than 6.
16. The electrode forming slurry composition according to claim 1 , further comprising lithium hydroxide.
17. 10. The electrode forming slurry composition of claim 1, wherein the polymer latex particles b) have a volume average particle size of less than 250 nanometers.
18. The electrode forming slurry composition of claim 1 , wherein the composition does not include carboxymethyl cellulose (CMC).
19. 10. The electrode-forming slurry composition of claim 1, wherein the composition does not include a polymer that includes a monomer that contains a conjugated double bond as a polymerized monomer.
20. 10. The electrode-forming slurry composition of claim 1, wherein the VOC content of said composition is 0 to less than 1% by weight.
21. 2. The electrode forming slurry composition according to claim 1, wherein the polymer latex particles b) have a Tg of 25° C. or less.
22. 2. The electrode-forming slurry composition according to claim 1, wherein the particulate anode-forming material a) comprises one or more materials selected from the group consisting of furnace black, acetylene black, ketjen carbon black, carbon nanotubes (CNTs), artificial graphite, natural graphite, hard carbon, soft activated carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semi-crystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate, and mixtures or composites thereof.
23. 23. An anode for use in an electrical energy storage device comprising a current collector coated on at least one side with the electrode-forming slurry composition of any one of claims 1 to 22 in dry form, the anode having a thickness of at least 10 microns and exhibiting a resistivity in the z-direction of less than 100 Ω cm.
24. 22. An electrical energy storage device comprising a non-aqueous electrolyte, the electrical energy storage device comprising at least one anode of claim 21, the electrical energy storage device being selected from the group consisting of a non-aqueous battery, a capacitor, and a membrane electrode assembly.